Comparative Study of the Thirteen Editions of the “Prontuario de ortografía de la lengua castellana” (1844-1866) by the Real Academia Española - Terrón Vinagre, Natalia (2024)
The Prontuario de ortografía de la lengua castellana of the Real Academia Española is a fundamental text in the history of Spanish orthography. It includes the official orthographic system for Spain’s education, and it was the only reference in terms of spelling in the academic field for more than two decades. In addition, its pedagogical nature separates this text from the treatises previously prepared. For this, the purpose of this research is the detailed analysis of the thirteen editions of the Prontuario (1844-1866), paying special attention to the differences it raises with respect to the latest orthography of the Real Academia Española (ORAE 1820), that is the starting point for the drafting of the school treatise. It is intended to clarify the value of this work both for the history of Spanish orthography, in general, and for the history of the RAE orthography, in particular.